2018
DOI: 10.1155/2018/8278039
|View full text |Cite
|
Sign up to set email alerts
|

CRP Stimulates GDF15 Expression in Endothelial Cells through p53

Abstract: Growth differentiation factor 15 (GDF15) is a multifunctional, secreted protein that is a direct target gene of p53. GDF15 is a prospective biomarker of cardiovascular disease (CVD). C-reactive protein (CRP), like GDF15, is implicated in inflammation and an independent biomarker of CVD. However, the molecular interactions between GDF15 and CRP remain unexplored. In women, we found a significant relationship between hsCRP and GDF15 serum and mRNA levels. In vitro treatment of cultured human aortic endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 53 publications
(62 reference statements)
0
26
0
Order By: Relevance
“…Correlation between MEG3 expression levels and clinical pathology in patients with pituitary adenoma. differentiation factor 15 (27,28). The expression of MEG3 is controlled by epigenetics and abnormal CpG methylation of MEG3 occurs in various types of tumor, such as cervical cancer and pituitary adenoma (23,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between MEG3 expression levels and clinical pathology in patients with pituitary adenoma. differentiation factor 15 (27,28). The expression of MEG3 is controlled by epigenetics and abnormal CpG methylation of MEG3 occurs in various types of tumor, such as cervical cancer and pituitary adenoma (23,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating Growth-and-Differentiation Factor 15 (GDF15) can reduce appetite 3 via specific receptors in the area postrema and nucleus tractus solitarius of the brainstem 4 . In the absence of acute illness, C-reactive protein (CRP) and insulin are among the endogenous GDF15 secretagogues, respectively in endothelial cells 5 and in the liver 6 . Metformin is an exogenous GDF15 secretagogue 7 9 , whose principal site of GDF15-releasing action is currently thought to be in the gut, in particular in the colon 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, Kim et al reported that the positive correlation between GDF-15 and C-reaction protein in a molecular level, which facilitated improved understanding of the pivotal inflammatory pathways important in CAD [20]. A recently published study observed an association of higher GDF-15 concentration with risk for mortality and heart failure in patients with CKD [21].…”
Section: Discussionmentioning
confidence: 99%